Pengembangan Computer-Based Test Sebagai Strategi Peningkatan Efisiensi Evaluasi Kegiatan Belajar Mengajar - Dedy Arisandi; Dian Rachmawati; Indra Aulia; Seniman Seniman (Juripol (Jurnal Institusi Politeknik Ganesha Medan), 2018)
One of the areas that can be a reference for the success and progress of a nation is the field of education. In the world of education, the examination has become one of the ways to measure learning achievement levels of students in the school. The examination that usually uses at school such as daily/weekly/monthly test, Midterm (UTS) and the Semester final exam (UAS). By using examination both students and teachers can evaluate each other about their teaching and learning activities. The examination model which used during this time is conventional methods model by using paper-based test. Traditional methods still have many shortcomings so that it takes another method for creating an efficient, effective, safe, accurate and fast test system. Another model which was already applied in the activities of the school students test is a method of Computer-Based Test (CBT Method). This way is proven to increase efficiency and effectiveness in the test. Unfortunately, this new approach is only applied to the activities of the national exam and have not been evenly distributed throughout the school. To use it in all the examination process such as daily/weekly/monthly test, Midterm (UTS) and the Semester final exam (UAS), the writer selected two school partners to implement CBT Exam in high school/Equal. Both schools are SMK Negeri 2 Binjai and MA "Mawaridussalam Deli Serdang. The target to be achieved is the creation of an alternative test method which can be used by the partner school that is more efficient, more effective, safer, more accurate and faster than old exam methods. The outcome which is to be accomplished is the creation of a system of computer-based test methods as an alternative method in the test of daily/weekly/monthly, UTS, and UAS on school partners by using PHP and My SQL.